(y/3)-1=(-5+7y)/3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 15:41:43
(y/3)-1=(-5+7y)/3(y/3)-1=(-5+7y)/3(y/3)-1=(-5+7y)/3原方程两边同乘以3可得:y-3=-5+7y-3+5=7y-y6y=2解得:y=1/3
(y/3)-1=(-5+7y)/3
(y/3)-1=(-5+7y)/3
(y/3)-1=(-5+7y)/3
原方程两边同乘以3可得:
y - 3=-5+7y
-3+5=7y-y
6y=2
解得:y=1/3
2(y-4)(3y+2)-5(-3y+7)(y+1),其中y=-1
3(y-3)-5(1+y)=7(y-1)
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
4(2y+5)-3y=7(y-5)+4(2y+1)
4(5—2y)+7(y+1)=3(4y-1)+17求y
4*(5—2y)+7(y+1)=3(4y-1)+17求y
[T,Y]=ode45(@rigid,[0 1],[rand(15,1)]);plot(T,Y(:,1),'-',T,Y(:,2),'-.',T,Y(:,3),'.',T,Y(:,4),'-',T,Y(:,5),'-.',T,Y(:,6),'.',T,Y(:,7),'-',T,Y(:,8),'-.',T,Y(:,9),'.',T,Y(:,10),'-',T,Y(:,11),'-.',T,Y(:,12),'-.',T,Y(:,13),'.',T,Y(:,14),'-',T,Y(:,15),'.')
(y-4)(3y+2)-(3y-7)(2y+1),其中y=4/3
解方程:3y^2-(2y+1)(y-1)=(y-5)(y+1)
解方程3y^2-(2y+1)(y-2)=(y-5)(y-1)
解方程:3y²-(2y+1)(y-2)=(y-5)(y+1)
5(y-2)-7(y+3)=11(y+4)
y-(y-1)/2=1-(2y-3)/5
y''-5y'+6y=3x+1通解
y-y-1/2=3-y+2/5
y=(y')^3+y'